The potentials of graffiti in opposing the women economic oppression: The Kosova case - Krasniqi, Artan; Haxhiu, Agnesa (SAUC - Street Art and Urban Creativity (repository), 2023)
Urban art in general, and graffiti in particular, has a multitude of artistic, cultural and social effects. Numerous studies explain its multidimensional role. This article specifically aims to address the potential that graffiti has in expressing revolt and opposition to the women economic oppression. Finally, the feminist movement in Kosova has started to use graffiti as a tool to raise concerns about the position of women in society. The study objective of this article is the graffiti that shows discrimination against women as the workforce on three levels: unpaid work, paid work at the public sector, as well as the illegal exploitation of paid work in the private sector.